2022
DOI: 10.2196/26779
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Gamification on Physical Activity: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background Gamification refers to the use of game elements in nongame contexts. The use of gamification to change behaviors and promote physical activity (PA) is a promising avenue for tackling the global physical inactivity pandemic and the current prevalence of chronic diseases. However, there is no evidence of the effectiveness of gamified interventions with the existence of mixed results in the literature. Objective The aim of this systematic review… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
83
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 74 publications
5
83
0
3
Order By: Relevance
“…By gamifying PA, participants are encouraged to move and walk to play, and this tends to make their activity more playful and motivating 20. A recent meta-analysis21 revealed that gamified interventions improved PA with an increase of more than 1600 daily steps. Importantly, additional analyses indicated that (1) gamified interventions appear more effective than equivalent non-gamified interventions and (2) PA improvement persists in the long-term 21.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By gamifying PA, participants are encouraged to move and walk to play, and this tends to make their activity more playful and motivating 20. A recent meta-analysis21 revealed that gamified interventions improved PA with an increase of more than 1600 daily steps. Importantly, additional analyses indicated that (1) gamified interventions appear more effective than equivalent non-gamified interventions and (2) PA improvement persists in the long-term 21.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis21 revealed that gamified interventions improved PA with an increase of more than 1600 daily steps. Importantly, additional analyses indicated that (1) gamified interventions appear more effective than equivalent non-gamified interventions and (2) PA improvement persists in the long-term 21. This suggests that gamification is more than a novelty effect, and that is a promising healthcare approach, as it can be easily implemented in daily life without adding demands to people’s schedules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article, “Evaluating the Effectiveness of Gamification on Physical Activity: Systematic Review and Meta-analysis of Randomized Controlled Trials” by Mazeas et al [ 1 ]. The authors conducted a systematic review and meta-analysis to evaluate the effectiveness of gamification on physical activity (PA).…”
mentioning
confidence: 99%
“…We appreciated and read with attention Hung and Kao’s [ 1 ] feedback on our recent systematic review and meta-analysis [ 2 ], which examined the effectiveness of gamified interventions on physical activity. These authors have pointed out 3 aspects that we will discuss in this letter.…”
mentioning
confidence: 99%